Modelo de poços quânticos para a transferência de elétrons - Jubilato, Karina Heloisa Paulino [UNESP] (2015)
The electron transfer occurs, for instance, in photosynthetic systems. Among these systems, the bacterial photosynthesis stands for being a cyclical process. The objective of this work is to propose a model of quantum wells to study the electrons transfer. The values used to deep of the potential and the size of each well are inspired by the photosynthetic purple bacterium Rhodobacter sphaeroides. From the suggested model it is possible to reproduce and to follow electron transfer in the reaction center of the bacterium. The proposed model consists in four asymmetric potential wells and the suggested method of calculation is to solve the problem two by two using the solution of the asymmetric double well. The eigenvalues of energy is obtained from a transcendental equation. The characteristic time of tunneling from each step of the process is determined from the Rabi formula. In this work, we obtain the analytical solution from independent of time Schrödinger equation for the bistable square symmetric and asymmetric one dimensional potential. For validation of the proposed method the triple square symmetric and asymmetric potentials are resolved